Greater Occipital Nerve Treatment in the Management of Spontaneous Intracranial Hypotension Headache: A Case Report - Niraj, G.; Critchley, Peter; Kodivalasa, Mahesh; Dorgham, Mohammed (Headache, 2017)
Background Clinical presentation of spontaneous intracranial hypotension headache (SIHH) has similarities with postdural puncture headache (PDPH). Recommended treatment for both conditions is an epidural blood patch. Successful outcomes following greater occipital nerve blocks have been reported in the management of PDPH. We present the first report of greater occipital nerve treatment in SIHH. Methods A 40‐year‐old male presented with a 2‐year history of daily postural headaches having a significant impact on quality of life. Magnetic resonance imaging revealed bilateral convexity subdural collections. Post gadolinium scan revealed pachymeningeal enhancement with reduced pontomesencephalic angle below 50 degrees. The patient was offered an epidural blood patch and greater occipital nerve block with corticosteroids. The patient chose occipital nerve block. Result The patient reported significant short‐term benefit lasting 4 months. Thereafter, the patient underwent pulsed radiofrequency treatment to bilateral greater occipital nerves. He reported significant benefit lasting 10 months. Conclusion Greater occipital nerve treatment may have a role in management of SIHH.